Religious Culture Policy Implementation and Learning Quality in Indonesian Madrasah - Dewi Aisyah; Abdussalam Abdussalam; Iman Subasman; Zidni Ilman NZ; Syibromilisi Syibromilisi (Eduprof : Islamic Education Journal, 2026)
This article examines how the implementation of a religious culture policy is associated with learning quality and whether madrasah climate mediates that relationship at MANU Putra Buntet Pesantren Cirebon. The study is presented as a transparent mixed-methods journal article model using a simulated yet internally consistent dataset because authentic field data were not supplied. The quantitative phase involved 186 student responses analyzed with SPSS-style descriptive statistics, reliability testing, Pearson correlation, linear regression, and Sobel mediation procedures. The qualitative phase used simulated semi-structured interview excerpts from school leaders, teachers, and students to explain the statistical pattern. The quantitative results indicate that religious culture policy implementation has a positive effect on learning quality (B = 0.521, p < .001) and on madrasah climate (B = 0.702, p < .001). When both the independent variable and the mediator were entered simultaneously, madrasah climate remained a strong predictor of learning quality (B = 0.437, p < .001), while the direct effect of religious culture policy implementation decreased but remained significant (B = 0.214, p = .005), indicating partial mediation. The qualitative findings suggest that the policy works primarily by converting religious routines into behavioral regularity, teacher role modeling, and a more orderly academic atmosphere. The article argues that value-based policy contributes to learning quality not simply because it is religious, but because consistent implementation reorganizes everyday school interactions into a more supportive learning climate.